Sacrococcygeal teratoma: a case report - Kumar, Nilay; Sinha, Avinash Kumar (International Surgery Journal, 2019)
Teratomas are germ cell tumours composed of multiple types of cells derived from more than a single germ cell layer. The most common site of an extra gonadal teratoma is the sacrococcygeal region. We report a case of a 10-day-old female child with a large swelling in the sacrococcygeal region extending laterally into the buttocks. X-ray showed a large mass projecting from the lower pelvic region and delineate the extent of the tumour and the involvement of tissues. Image findings and clinical presentation led to the diagnosis of sacrococcygeal teratoma. Tumour was surgically excised with prior pre-anaesthetic checkup, post-operative period was uneventful. She was discharged with advice to come in follow-up surgical outpatient clinic. There was no evidence of tumour recurrence till 1 year of age. She had normal growth curve for her age with normal developmental milestones.